Obstetric violence and misinformation of parturients - Silva, Sâmela Osório de Lima e (2023)
Obstetric violence is a relatively new topic, but one that has been popular for a long time. The lack of empathy, the lack of instructions, and the disrespect towards the patient at a delicate moment, and among other related complaints, are often necessary for patient safety in order to avoid incidents such as those that will be mentioned. To address and identify actions that are related to obstetric violence during care during the pregnancy-puerperal cycle. The continuing education of obstetricians is considered of paramount importance in order to pass on the necessary knowledge to their team and to the pregnant woman in view of their rights to all proposed. Bibliographic, quantitative review, comprising the search engines Google academic, Scielo and a publication in Lilacs, dated from 2014 to 2021. It is observed the emergence of a challenging problem in the field of nursing, with a delicate subject almost never discussed, when in most cases many women have already experienced some type of obstetric violence. The impacts caused by obstetric violence, complaints about the treatments received, the lack of information about the situation and the importance of a safe childbirth. In view of the code of ethics of health professionals, especially nurses and obstetricians, it is their duty to care for, support and serve their patients with decorum and professionalism.